Reporting on Non-Financial Information According to the SIN Structure - Błażyńska, Joanna (Studia Oeconomica Posnaniensia, 2019)
The theory and practice of accounting for the second decade of the 21st century focuses in particular on the usefulness of non-financial information for stakeholders in the process of making business decisions and attempting to codify them. Hence a number of initiatives in the form of norm, principles, guidelines and standards to help individuals report on non-financial information. The article attempts to define from a theoretical and practical perspective changes in reporting on non-financial information, as a consequence of the implementation of Directive 2014/95 / EU, using the Polish Standard for Non-Financial Information (SIN). The analysis was reported in accordance with art. 49b of the Accounting Act, non-financial information for the years 2017 and 2018 of three entities from the IT industry. The analysis covered: compliance of information disclosures with the SIN structure, application of key indicators and qualitative changes of reported non-financial information. Consequences show how, on the basis of the same statutory record, individuals differently approach disclosing non-financial information.